Rethinking Unjust Enrichment: Advancing Distributive Justice in Indonesian Law: Memikirkan Kembali Unjust Enrichment: Memajukan Keadilan Distributif dalam Hukum Indonesia - Puspatara, Rian Ganggas; Kurniawan, I Gede Agus (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to analyze the development of the unjust enrichment doctrine in Indonesia from a progressive legal perspective. Employing normative legal research with conceptual, comparative, and legislative approaches, the study confirms that the philosophical orientation of the unjust enrichment doctrine in Indonesian civil law is expected to optimize the idea of distributive justice, which is relevant in civil practice. The actualization of the unjust enrichment doctrine in a progressive legal perspective can be achieved through philosophical, theoretical, and practical approaches. By exploring the principles of proportionality and Pancasila values as Indonesia's legal ideals, integrating the development of unjust enrichment doctrine within the theoretical framework of tortious acts, and promoting the active and creative utilization of Article 1359 of the Indonesian Civil Code, this study offers insights for judges and legal practitioners in their pursuit of justice in civil cases based on unjust enrichment claims.Highlights: Philosophical orientation: Emphasizes distributive justice and embraces Pancasila values as Indonesia's legal ideals. Theoretical development: Integrates unjust enrichment doctrine within the framework of tortious acts. Practical approach: Encourages active and creative utilization of Article 1359 of the Indonesian Civil Code by judges and legal practitioners. Keywords: unjust enrichment, progressive legal perspective, distributive justice, Indonesian civil law, Pancasila values